Direct CRISPR spacer acquisition from RNA by a natural reverse-transcriptase-Cas1 fusion protein - Silas, Sukrit (Science, 2016)
CRISPR (Clustered Regularly Interspaced Short Palindromic Repeat) systems mediate adaptive immunity in diverse prokaryotes. CRISPR-associated Cas1 and Cas2 proteins have been shown to enable adaptation to new threats in Type I and II CRISPR systems by the acquisition of short segments of DNA (“spacers”) from invasive elements. In several Type III CRISPR systems, Cas1 is naturally fused to a reverse transcriptase (RT). In the marine bacterium Marinomonas mediterranea (MMB-1), we show that an RT-Cas1 fusion enables the acquisition of RNA spacers in vivo in an RT-dependent manner. In vitro, the MMB-1 RT-Cas1 and Cas2 proteins catalyze ligation of RNA segments into the CRISPR array, followed by reverse transcription. These observations outline a host-mediated mechanism for reverse information flow from RNA to DNA.